Evaluasi Hasil Belajar Pendidikan Agama Islam (PAI) Melalui Library Research - Faelasup Faelasup; Aprianti Astuti (Pusat Riset dan Inovasi Nasional, 2025)
This article discusses the evaluation of learning outcomes in Islamic Religious Education (PAI) through a library research approach. Evaluation is a crucial component of the learning process, as it measures the extent to which learning objectives cognitive, affective, and psychomotor have been achieved. In practice, PAI evaluations still tend to emphasize the cognitive aspect, while the affective and psychomotor domains receive less attention. Findings from various literature sources emphasize the importance of holistic evaluation that comprehensively assesses all learning domains. Alternative methods such as observation, portfolios, reflective journals, self-assessment, and religious project-based evaluations are recommended to capture students' learning outcomes more accurately. However, implementation challenges persist, including limited time, insufficient teacher training, and a lack of appropriate evaluation tools. Therefore, this article recommends enhanced teacher capacity-building, supportive policies, and innovation in evaluation systems so that PAI assessment moves beyond administrative formality and effectively fosters students’ Islamic character development in a holistic manner